„Nad przepaścią” (Над пропастью). Рисунки неизвестной польской девушки, сосланной в Казахстан - Borissova, Anna; Legkiy, Dmitriy; Chazbijewicz, Selim (Przegląd Wschodnioeuropejski, 2023)
The authors are the first to introduce declassified archival materials, documents of the Special State Archive of the Kostanay region Department of the National Security Committee of the Republic of Kazakhstan, including paintings withdrawn in 1942 by the NKVD, into scientific discourse. January 1941 paintings of an unknown deported Polish girl give us an opportunity to understand the conditions in which deported Poles found themselves in the Kostanay region of the Kazakh SSR in the first years of World War II. The article attempts to reveal the secret of this mysterious story. The published documents concerning the Kostanay region relate only to the period of the Great Patriotic War but do not include the time of the deportation of Poles in 1940. Thus, this publication allows us to fill a significant gap in the study of this issue.